2014
DOI: 10.1155/2014/283034
|View full text |Cite
|
Sign up to set email alerts
|

The Shifts of Band Gap and Binding Energies of Titania/Hydroxyapatite Material

Abstract: The titania/hydroxyapatite (TiO 2 /HAp) product was prepared by precipitating hydroxyapatite in the presence of TiO(OH) 2 gel in the hydrothermal system. The characteristics of the material were determined by using the measurements such as X-ray photoemission spectroscopy (XPS), X-ray diffraction (XRD), diffuse reflectance spectra (DRS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX). The XPS analysis showed that the binding energy values of Ca (2p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The peak in Figure c at 399.3 eV due to the N 1s peak corroborates positively with quinoid amine and benzenoid amine, which is consistent with the structure of PANI as reported by Golczak et al Figure d presents the core level O 1s spectra (530 eV) due to O bonds such as Ti–O–Ti and Ti–O–H . Ti 2p core level spectra are presented in Figure e at 459.2 eV and 464.9 eV due to Ti 2p 1/2 and Ti 2p 3/2 , respectively. , …”
Section: Resultsmentioning
confidence: 99%
“…The peak in Figure c at 399.3 eV due to the N 1s peak corroborates positively with quinoid amine and benzenoid amine, which is consistent with the structure of PANI as reported by Golczak et al Figure d presents the core level O 1s spectra (530 eV) due to O bonds such as Ti–O–Ti and Ti–O–H . Ti 2p core level spectra are presented in Figure e at 459.2 eV and 464.9 eV due to Ti 2p 1/2 and Ti 2p 3/2 , respectively. , …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Sections and 4.2, synthesized powders can be characterized as Ti-modified hydroxyapatites, containing Ti-doped hydroxyapatite and titanium-bearing amorphous or crystalline impurity phases. As follows from DR spectroscopy data (Section ) and previous studies, ,, modification of HAp by titanium leads to an emergence of absorption edge in the UV area with the respective red shift. The red shift is more pronounced at higher contents of titanium ions.…”
Section: Discussionmentioning
confidence: 74%
“…Researching on the acetaldehyde gas decomposition of TiHAp by UV with VIS irradiation, the authors investigated the increase of activity comparing with when UV irradiation alone was used. Linh et al [46] also indicated the shift of bandgap of TiO 2 /HAp material synthesized by the hydrothermal process containing TiO(OH) 2 and HAp gels. The binding energy values of Ca 2p, P 2p, and O1s levels are related to hydroxyapatite phase, whereas those of Ti 2p levels corresponded with the characterization of titanium (IV) in TiO 2 .…”
Section: The Promoted Impact Of Hydroxyapatite In the Photocatalytic mentioning
confidence: 98%